OPTIMIZING ANTIPSYCHOTIC USE IN RESIDENTIAL CARE: THE ROLE OF ORGANIZATIONAL READINESS FOR CHANGE. (11th November 2018) - Smith, A; Kurucz, S; Dawkes, A; Kampen, R; Erb, T
Abstract: Persons with dementia (PwD) experience challenging neuropsychiatric symptoms (NPS) as their illness progresses. Antipsychotic drugs (APD) have been regularly used in residential care to manage this issue despite the risk of adverse events and increased morbidity and mortality. This study examines the role of culture of care in relation to continued inappropriate APD use when managing NPS in PwD. Culture of care consists of sets of norms, beliefs, and cognitive frames which inform clinical practice and care delivery. The study also considers organizational readiness for change in examining the implementation of alternate non-pharmaceutical practices to address the issue of NPS. Findings were obtained from three Canadian residential care facilities that worked on reducing inappropriate use of APD. Data came from interviews with 16 licenced practical nurses, 12 nurses, 17 health care assistants, 3 activity leaders, 3 directors of care, 10 physicians, and 14 family members. We found that care providers varied in their perceived capacity to implement novel care strategies and in the support received for innovative thinking and action. We also identified variations in how care providers informally share information on alternate strategies to manage NPS and in the contextual factors facilitating such communication. Finally, we found differences in how family members' input was meaningfully integrated into care planning. Overall, the study shows how culture of care reflects entrenched responses to NPS but also evolves to support challenges to the decision to prescribe APD, non-pharmaceutical approaches to care, and the meaningful involvement of family members in care planning.